ADVANCE CARE PLANNING IN MENTAL HEALTH: LEGAL ISSUES AND NEW DEVELOPMENTS. Issue 2 (1st June 2013) - Weller, P
Abstract : Background: Advance Care Planning (ACP) in mental health raises a series of unique legal questions. Writing about 'advance statements' in Scotland, Jacqueline Atkinson identified them as the questions of nomenclature, capacity, content and legal status (Atkinson 2003). International comparisons of ACP in mental health shows that the broader human rights context in which mental health laws operate also influences the scope and interpretation of the key issues that underpin ACP practice. Aim: The aim this paper is to indentify prominent legal issues in ACP in mental health in Australia in light of the growing impact of the Convention on the Rights of Persons with Disabilities (CRPD). Methods: The analysis is based on the author's research as Post Doctoral Research Fellow and Deputy Director of the Centre for the Advancement of Law and Mental Health in the Faculty of Law at Monash University. This paper will discuss the four key issues by presenting an analysis on international and Australian jurisprudence with respect to the question of mandated housing and accommodation for people with mental health problems. Discussion: This approach highlights recent developments in the law, shedding light on the relationship between compulsory mental health laws and the common law. It illustrates the emerging recognition in law that the preferences of the person have significance in care and treatment decisions, highlighting areas of law and practice that remain uncertain. Conclusion: The paper argues that ACP practice in mental health will be facilitated by practical research into the law and its effects.